2006
DOI: 10.1002/jrs.1563
|View full text |Cite
|
Sign up to set email alerts
|

Dimerisation and vibrational spectroscopic properties of (RS)-phenylsuccinic acid

Abstract: Single crystals of (RS)-phenylsuccinic acid (RSPSA) were grown by the slow evaporation technique and vibrational spectral analysis was carried out using near-IR Fourier transform Raman and Fourier transform IR spectroscopy. The density functional theoretical (DFT) computations were also performed at the B3LYP/6-31G(d) level to derive the equilibrium geometry, vibrational wavenumbers, intensities and atomic charges. Vibrational spectral investigation confirmed the formation of cyclic dimers in the crystal, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The broadening in the O-H stretching of SPSA is due to combination bands between the low wavenumber vibrations and ν O-H and between the ring vibrations and excited binary combination of δ COH and ν C-O . The weak bands in infrared spectrum 2700-2500 cm -1 region, correspond to overtones and combinations of the 1322 and 1423 cm -1 bands due to interacting C-O stretch and O-H deformation vibrations 19,[27][28][29][30][31][32][33][34][35][36]. The very strong Raman peak at 1292 cm -1 is due to the O-H in-plane deformation mode as expected.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The broadening in the O-H stretching of SPSA is due to combination bands between the low wavenumber vibrations and ν O-H and between the ring vibrations and excited binary combination of δ COH and ν C-O . The weak bands in infrared spectrum 2700-2500 cm -1 region, correspond to overtones and combinations of the 1322 and 1423 cm -1 bands due to interacting C-O stretch and O-H deformation vibrations 19,[27][28][29][30][31][32][33][34][35][36]. The very strong Raman peak at 1292 cm -1 is due to the O-H in-plane deformation mode as expected.…”
mentioning
confidence: 65%
“…Owing to its rather rigid structure, benzoic acid can be regarded as a good model compound in the investigation of interaction of carboxylic acids with metal surfaces. 8 Vibrational and SERS spectral investigations of (RS)-phenylsuccinic acid 19,20 supported by ab initio density functional theory studies have been reported. Though the crystal structure of the title compound, (S)-phenylsuccinic acid (SPSA) has been reported, 21 the vibrational spectral features of SPSA crystal have not been subject of detailed analysis so far.…”
Section: Introductionmentioning
confidence: 98%
“…Peaks at 1110, 1149, 1202 and 1757 cm 1 can be assigned to the stretching vibration of O-H and C-O, while peaks at 1336, 1520, 1589 and 2219 cm 1 correspond to the C C vibration in the aromatic ring. 15,16 Earlier Raman spectroscopic studies revealed that the Raman spectra of pristine carbon fiber consist of characteristic peaks at ¾1350 and 1580 cm 1 . The notable differences found on the sample CF are believed to be due to the sizing on the fiber surface applied by the manufacturer.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrational spectroscopy has been extensively used to understand the factors contributing to the vibrational modes in organic materials and to obtain deeper knowledge regarding intermolecular interactions. [17,18] NIR FT-Raman and FT-IR spectra, combined with density functional theoretical computations, have recently been successfully employed in the vibrational spectral analysis of drug molecules, biological compounds and natural products, since fluorescence-free Raman spectra and computed results help in the unambiguous identification of vibrational modes and provide deeper insight into the bonding and structural features of complex organic molecular systems. [19 -21] The present work describes the geometrical optimization and vibrational spectral investigations on the relationship between the molecular structural features of the CA2 molecule, with special emphasis on the role of the ICT mechanism in such organic materials.…”
Section: Introductionmentioning
confidence: 99%